2020
DOI: 10.1111/lam.13263
|View full text |Cite
|
Sign up to set email alerts
|

Ready‐to‐eat street food: a potential source for dissemination of multidrug‐resistant Escherichia coli epidemic clones in Quito, Ecuador

Abstract: Significance and Impact of the Study: This study identified ESBL-producing Escherichia coli epidemic clones: ST131, ST410 and ST744 in ready-to-eat street food samples. Street food is a possible way to spread harm multidrug-resistant (MDR) E. coli strains in the community. Studies to identify the contamination sources of this kind of food are needed to tackle MDR E. coli dissemination. AbstractReady-to-eat food contamination with ESBL-producing Escherichia coli is a growing health concern. Some of these strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
2
21
0
2
Order By: Relevance
“…The ESBL‐producing E. coli in this study belonged to a diversity of genotypes. E. coli ST162, isolated from goat faeces in this study, has been identified producing a number of different CTX‐M variants in food such as chicken meat in Japan and street food in Ecuador (Hayashi et al., 2018; Zurita et al., 2020), as well as in healthy livestock and diseased companion animals (Dahms et al., 2015; Zhang et al., 2019), indicating that E. coli ST162 may be associated with the dissemination of bla CTX‐M genes in the food chain. Notably, E. coli ST162 has been reported to cause diarrhoea in children (Zhang et al., 2016), pointing to its pathogenic potential.…”
Section: Discussionmentioning
confidence: 85%
“…The ESBL‐producing E. coli in this study belonged to a diversity of genotypes. E. coli ST162, isolated from goat faeces in this study, has been identified producing a number of different CTX‐M variants in food such as chicken meat in Japan and street food in Ecuador (Hayashi et al., 2018; Zurita et al., 2020), as well as in healthy livestock and diseased companion animals (Dahms et al., 2015; Zhang et al., 2019), indicating that E. coli ST162 may be associated with the dissemination of bla CTX‐M genes in the food chain. Notably, E. coli ST162 has been reported to cause diarrhoea in children (Zhang et al., 2016), pointing to its pathogenic potential.…”
Section: Discussionmentioning
confidence: 85%
“…Here, bla CTX–M–65 is identified in Portugal for the first time in food of animal origin, with no reports linking to human infections; a complete characterization by WGS of the four MDR E. coli harboring this gene is described. E. coli harboring the bla CTX–M–65 gene is commonly found in food-producing animals and meat from Southwest Asian and South American countries ( Rao et al, 2014 ; Na et al, 2019 ; Vinueza-Burgos et al, 2019 ; Zurita et al, 2019 ). Although rarely occurring in Europe, previous studies have reported CTX-M-65-producing E. coli from Dutch beef calves ( Ceccarelli et al, 2019 ) and wild birds from Switzerland ( Zurfluh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, E. coli ST2179 bearing the bla CTX–M–65 gene but belonging to phylogroup A was reported from ducks in South Korea ( Na et al, 2019 ). Isolates belonging to phylogroup B1 are commonly associated with non-pathogenic commensal E. coli reported from humans, animals, and food products ( Bailey et al, 2010 ; Coura et al, 2015 ; Scheinberg et al, 2017 ; Belaynehe et al, 2018 ; Zurita et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, commensal strains and obligatory pathogens belong to the phylogroups A and B1, whereas strains with extended virulent attributes (mainly ExPEC) are part of the phylogroups B2, D, and F, with the latter as a sister group of B2 (Escobar-Páramo et al, 2004;Clermont et al, 2013). Multi-locus sequence typing (MLST) allows additional classification and several phylogenetic studies suggest the spread of pandemic high-risk clonal lineages including primarily sequence type (ST) 131 (Nicolas-Chanoine et al, 2008;Ewers et al, 2010;Hussain et al, 2012), ST648 (Ewers et al, 2014;Schaufler et al, 2019), ST410 (Schaufler et al, 2016b;Zurita et al, 2020), putatively ST405 (Manges et al, 2019), and others.…”
Section: Introductionmentioning
confidence: 99%